Indigenous Child Wellness: A Scoping Review of Best Practices with Initial Advising from Indigenous Community Members on Contextual Considerations and Next Steps - Levasseur-Puhach, Sydney; Bonin, Lynette; Hunter, Sandra; Roos, Leslie (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2024)
The measurement of wellness among Indigenous Peoples is crucial to understanding the needs of communities today and for generations to come. Here, we summarize the extant research on assessments relevant to measuring the wellness of Indigenous children in Canada through an examination of existing international best-practices. A thoughtful identification of wellness metrics aligned with Indigenous cultural contexts is important because in the past, wellness assessments that were not co-developed by Indigenous partners have perpetuated systemic harms. A scoping review of existing measures across Canada, the United States, Australia and New Zealand was completed consistent with the PRISMA guidelines across five databases. These guidelines provided guidance for the process of the review, as well as the structure for this paper. Search terms included "Indigenous" or "Aboriginal”, "wellness", “child-welfare”, "children”, “families" and “framework” or “measure”. In total 896 abstracts were screened. Of these, 88 articles were reviewed, 16 measures and four frameworks were identified as most relevant to our work. All efforts were led by Indigenous students in keeping with Traditional Ways of Being and Knowing as well as self-determination practices. Semi-structured interviews were also conducted with four Indigenous community members in order to advise the process of developing such a project and to gauge considerations on the appropriateness of assessing wellness in our communities. Results highlight a unique set of factors to consider from an Indigenous values perspective when assessing child wellness. The most salient of these include incorporating elements of self-determination in both measure development and usage. Themes of family, community, and wholism were also emphasized. While this exemplifies an emerging assessment base for measuring wellness, minimal work to date is directly designed to be relevant for Indigenous children or youth. Moving forward, we will seek to fill this gap by supporting the development of a wellness measure with potential to multi-contextual relevance to promote the adequate and equitable dispersion of supports and resources to families and communities.